Keefektifan Model Pembelajaran Kooperatif Tipe Picture and Picture Berbantuan Quizizz Terhadap Hasil Belajar IPA Kelas IV Sekolah Dasar - Faiqotus Saidah; Muslimin Ibrahim; Thamrin Hidayat; Asmaul Lutfauziah (Departement of Mathematics Education, 2024)
This research is motivated by the low student learning outcomes which are often caused by the lack of variety in learning models and methods, thus reducing student interactivity. The main focus of learning activities is to achieve optimal learning outcomes through active student participation by utilizing advanced technology so that students are more active in the learning process. This study aims to determine the effectiveness of the Picture and Picture Type Cooperative learning model assisted by Quizizz on science learning outcomes. The method used in this research is descriptive quantitative with a one group pretest posttest design. The research targets amounted to 15 students. Data collection techniques include observation and tests. The results showed that the implementation of science learning in elementary schools using this learning model was 100% implemented. The increase in the average score from 61.33 (pretest) to 87.33 (posttest) shows the effectiveness of the model used. Science learning through this learning model is very effective, because the student completeness value has reached at least 75%. Based on the overall data analysis, there was a significant increase from pretest to posttest with an average value of 0.6744. The average value of N-Gain is in the moderate category because it is in the range of 0.3 ≤ N-Gain < 0.7. The implication of this study is that teachers can use this learning model to improve student learning outcomes and for other researchers it is recommended that they want to conduct replication research to see the consistency of the results that have been achieved.